Adsorbed p‐Aminothiophenol Molecules on Platinum Nanoparticles Improve Electrocatalytic Hydrogen Evolution. Issue 15 (6th January 2023) - Wang, Jin; Yu, Jinhong; Wang, Junjie; Wang, Kaili; Yu, Liuyingzi; Zhu, Chengcheng; Gao, Kun; Gong, Zhongyan; Li, Zhuoyao; Devasenathipathy, Rajkumar; Cai, Dongyu; Xie, Haijiao; et al.
Abstract: Electrocatalytic hydrogen evolution is an important approach to produce clean energy, and many electrocatalysts (e.g., platinum) are developed for hydrogen production. However, the electrocatalytic efficiency of commonly used metal catalysts needs to be improved to compensate their high cost. Herein, the electrocatalytic efficiency of platinum nanoparticles (PtNPs) in hydrogen evolution is largely improved via simple surface adsorption of sub‐monolayer p ‐aminothiophenol (PATP) molecules. The overpotential goes down to 86.1 mV, which is 50.2 mV lower than that on naked PtNPs. This catalytic activity is even better than that of 20 wt.% Pt/C, despite the much smaller active surface area of PATP‐adsorbed PtNPs than Pt/C. It is theoretically and experimentally confirmed that the improved electrocatalytic activity in hydrogen evolution can be attributed to the change in electronic structure of PtNPs induced by surface adsorption of PATP molecules. More importantly, this strategy can also be used to improve the electrocatalytic activity of palladium, gold, and silver nanoparticles. Therefore, this work provides a simple, convenient, and versatile method for improving the electrocatalytic activity of metal nanocatalysts. This surface adsorption strategy may also be used for improving the efficiency of many other nanocatalysts in many reactions. Abstract : Electrocatalytic efficiency of PtNPs in hydrogen evolution is largely improved via surface adsorption of p ‐aminothiophenol (PATP) molecules. The improved electrocatalytic activity can be attributed to the change in electronic structure of PtNPs induced by surface adsorption of PATP molecules. This strategy may also be used for improving the efficiency of many other nanocatalysts in many reactions.